Perubahan Komposisi Gulma pada Sistem Tumpangsari Padi Gogo dengan Kedelai di Lahan Pasir Pantai - Putra, Fajrin Pramana; Yudono, Prapto; Waluyo, dan Sriyanto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Weeds can reduce upland rice yields in coastal sandy area. Density and growth of weeds can be controlled and reduced by an intercropping system between upland rice with soybeans. The study aimed to determine the weeds composition change and weeds biomass in various crop proportions of upland rice and soybean under intercropping. The research was conducted from December 2016 until March 2017, at coastal sandy soil of Samas, Bantul, Yogyakarta (8°00’03.5”S and 110°15’20.1”E). This study used a complete randomized block design (RCBD) with one factor and three replications. The treatments were crop proportions of upland rice and soybean under intercropping with 6 levels, such as 100:0 (upland rice monoculture), 80:20, 60:40, 40:60, 20:80, and 0: 100 (soybean monoculture). The results showed that there was weeds composition changes due to setting crop proportions of upland rice and soybean under intercropping at coastal sandy soil. Weed of sedges, grass, and broadleaf were found throughout the experimental plots, but varied in number and type of weeds among experimental plots. Weeds condition differed among the soybean proportion treatments < 40% and  ≥ 40%. The average community coefficient value was <75% which was dominated by Digitaria nuda and Eragrostis tenella under soybean proportion treatments < 40%, and Ludwigia parviflora and Amaranthus lividus under soybean proportion treatments ≥ 40%. The linear model was established between the increase of soybean proportion to a decrease in dry weight of weeds as Y = -0.6624X + 67.699; R2 = 0.7224).Keywords: crops proportion, intercropping, weeds community